PERILAKU PEGAWAI INSTALASI PEMELIHARAAN SARANA RUMAH SAKIT DALAM MENUNJANG PELAYANAN DI RSUP PROF. DR. R. D. KANDOU MANADO - Mananohas, Melky; Kimbal, Marthen; Londa, Very (Sam Ratulangi University, 2017)
Abstract: existing Employees in Installation Maintenance Means obligations which has Hospitals in planning, organizing, funneling up to perform maintenance means the hospital. Because quality health care embodies not only with regard to the quality of service of the medical but also through the support staff in the maintenance of medical equipment, medical and building. This research was conducted to analyze the cause of the behavior of employees in the installation maintenance facility is not yet supporting a Ministry Hospital Prof. Dr. R. D. Kandou Manado in the study of management science of public administration. By using qualitative design found that the causes are not yet as good behavior of the installation Maintenance employee Means a General Hospital Center of Prof. Dr. R. D. Kandou relating to the capabilities, needs, beliefs, work experience and expectation of employees itself. Key Words: Behavior, Employees, Maintenance Facility. The Hospital.